Prevalence of developmental dysplasia of the hip (DDH) in infants: a systematic review and meta-analysis - Jie Wang; Bowen Li; Yuanyuan Li; Jianglin Zhang; Junqiang Yang; Xiaoli Yan; Zhongbin Tao; Yanming Li; Yongkang Zhou; Huili Liu; Jizu Ling; Yijie Pei (BMJ Publishing Group, 2023)
Objective To estimate the prevalence of developmental dysplasia of the hip (DDH) in infants with a systematic review and meta-analysis.Method A literature search was conducted in April 2023, using databases such as Cochrane Library, PubMed, MEDLINE, CNKI, and SinoMed, without language restrictions. Eligible studies included cross-sectional studies reporting the prevalence of DDH among infants aged 0-12 months. Two independent reviewers manually selected and coded the studies, with any disagreements resolved by a third reviewer. Meta-analysis was performed using a random-effects model to calculate the prevalence of DDH. Regression analysis examined the trend of DDH prevalence, and stratification analysis explored heterogeneity between studies.Results A total of 65 studies involving 3 451 682 infants were included in the meta-analysis. None of the studies were classified as high quality, four were medium-to-high quality, 50 were low-to-medium quality, and eight were low quality. The pooled prevalence of DDH was 1.40% (95% CI: 0.86 to 2.28, I2=100%), and prevalence of dysplasia, subluxation, and dislocation was 1.45% (95% CI: 0.93 to 2.24, I2=97%), 0.37% (95% CI: 0.22 to 0.60, I2=94%), and 0.21% (95% CI: 0.13 to 0.34, I2=92%), respectively. Notably, the overall prevalence has a slight upward trend in the last three decades (β=0.24, p=0.35), but the dysplasia was downward trend (β=−0.48, p<0.01). Girls have higher risk of DDH than boys (1.46% vs 0.66%; Q=5.83, df=1, p=0.02). There were no significant differences based on gender, country, setting, or screening technique.Conclusion The prevalence of DDH among infants is approximately one in a 100, with girls being at higher risk. Though the prevalence of dysplasia has decreased, there is a slight upward trend in overall DDH. Therefore, routine screening for DDH in infants is recommended to prevent more serious developmental problems.